MHD forced convection boundary layer slip flow in Darcy-Forchheimer porous medium with effects of chemical reaction - Abu Bakar, Shahirah; Md. Arifin, Norihan; Md Ali, Fadzilah; Nazar, Roslinda (Praise Worthy Prize, 2014)
A mathematical model of MHD forced convection boundary layer with first order chemical reaction of an incompressible fluid past a plate embedded in a Darcy-Forchheimer porous medium. Velocity and thermal slips are considered instead of no-slip conditions at the boundary. The governing partial differential equations are transformed into ordinary differential equation using self-similarity transformation which are then solved numerically with shooting method. A parametric study of the physical parameters involved in the problem is conducted and representative set of numerical results are presented through graphs and tables, and are discussed. It is observed that the concentration boundary layer thickness decreases with increasing of Schmidt number and reaction-rate parameter.